The lysyl oxidases LOX and LOXL2 are necessary and sufficient to repress E-cadherin in Hypoxia: Insights into cellular transformation processes mediated by HIF-1 - Schietke, Ruth; Warnecke, Christina; Wacker, Ingrid; Schödel, Johannes; Mole, David R.; Campean, Valentina; Amann, Kerstin Ute; Goppelt-Strübe, Margarete; Behrens, Jürgen; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Journal of Biological Chemistry, 2010)
Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously demonstrated LOX, we characterize LOXL2 as a direct transcriptional target of HIF-1. We demonstrate that activation of lysyl oxidases is required and sufficient for hypoxic repression of E-cadherin, which mediates cellular transformation and takes effect in cellular invasion assays. Our data support a molecular pathway from hypoxia to cellular transformation. It includes up-regulation of HIF and subsequent transcriptional induction of LOX and LOXL2, which repress E-cadherin and induce epithelial to mesenchymal transition. Lysyl oxidases could be an attractive molecular target for cancers of epithelial origin, in particular because they are partly extracellular. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2024-05-13